Contribution to the Development of a Simulation Model for a Seaport in Specific Operating Conditions - Dundović, Čedomir; Bilić, Mirko; Dvornik, Joško (Promet - Traffic&Transportation, 2012)
The purpose of this paper is to show the efficiency of application of system dynamic simulation modelling when researching the behaviour dynamics of the port transhipment process, and finding the optimal solution for cargo handling with regard to the type and scope of cargo traffic, directions of movement, and pace of receiving and shipping of cargo. In view of the potential scientific implementation and verification of the hypotheses about the usage of system dynamic simulation models, the goals are multi-dimensional as they include designing qualitative and quantitative simulation models for a non-linear system, verification of the validity of the behaviour dynamics of the model, application of the simulation models, application of the parameter optimisation of the simulated process, and scientific verification of the results obtained through the simulation of the model. In compliance with the developed system-dynamic, mental-verbal and structural model, using the Powersim Studio system-dynamic flowchart of the port cargo system, in Powersim Studio simulation language, it is possible to conduct a scientific research of the dynamics of the continuous behaviour of the observed port cargo system in an experimental way, i. e. by using computers, simulating various scenarios of likely occurrences in the real world, without jeopardising it.KEY WORDS: system dynamics, modelling, transhipment process, optimisation, continued and discrete simulation